SIRAMAN MANTEN GAGRAG SURAKARTA DALAM PERSPEKTIF HINDU - Pratisthita, Shinta Tyas (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
The aim of this research is to describe the procession and meaning contained in the Gagrag Surakarta siraman manten ceremony and perspectives in Hindusim. This research was conducted in Dompyongan, Jogonalan, Klaten. The data sources for this research are informants from cultural experts and Hindu religious figures in Dompyongan Village. Data collection uses in-depth interviews. Validity test uses theoretical triangulation techniques and data source triangulation. From the results of data analysis, it was found that the siraman manten gagrag procession in Surakarta included: sungkeman, siraman, mecahake kendhi, cut rikma, and bopongan. In the Hindu religious perspective, this procession has the meaning and purpose of ensuring that the bride and groom always obtain safety and remain physically and mentally happy with their partner and become a shukino bhavantu family. keyword : Siraman, Hindu perspective, manten garag Surakarta